Local Electric Field-Incorporated In-Situ Copper Ions Eliminating Pathogens and Antibiotic Resistance Genes in Drinking Water - Ruiqing Li; Haojie Dai; Wei Wang; Rulin Peng; Shenbo Yu; Xueying Zhang; Zheng-Yang Huo; Qingbin Yuan; Yi Luo (Antibiotics)
Background/Objectives: Pathogen inactivation and harmful gene destruction from water just before drinking is the last line of defense to protect people from waterborne diseases. However, commonly used disinfection methods, such as chlorination, ultraviolet irradiation, and membrane filtration, experience several challenges such as continuous chemical dosing, the spread of antibiotic resistance genes (ARGs), and intensive energy consumption. Methods: Here, we perform a simultaneous elimination of pathogens and ARGs in drinking water using local electric fields and in-situ generated trace copper ions (LEF-Cu) without external chemical dosing. A 100-μm thin copper wire placed in the center of a household water pipe can generate local electric fields and trace copper ions near its surface after an external low voltage is applied. Results: The local electric field rapidly damages the outer structure of microorganisms through electroporation, and the trace copper ions can effectively permeate the electroporated microorganisms, successfully damaging their nucleic acids. The LEF-Cu disinfection system achieved complete inactivation (>6 log removal) of Escherichia coli O157:H7, Pseudomonas aeruginosa PAO1, and bacteriophage MS2 in drinking water at 2 V for 2 min, with low energy consumption (10−2 kWh/m3). Meanwhile, the system effectively damages both intracellular (0.54~0.64 log) and extracellular (0.5~1.09 log) ARGs and blocks horizontal gene transfer. Conclusions: LEF-Cu disinfection holds promise for preventing horizontal gene transfer and providing safe drinking water for household applications.